Microevolutionary, macroevolutionary, ecological and taxonomical implications of punctuational theories of adaptive evolution - Flegr, Jaroslav (BioMed Central, 2013)
ABSTRACT: Punctuational theories of evolution suggest that adaptive evolution proceeds mostly, or even entirely, in the distinct periods of existence of a particular species. The mechanisms of this punctuated nature of evolution suggested by the various theories differ. Therefore the predictions of particular theories concerning various evolutionary phenomena also differ. Punctuational theories can be subdivided into five classes, which differ in their mechanism and their evolutionary and ecological implications. For example, the transilience model of Templeton (class III), genetic revolution model of Mayr (class IV) or the frozen plasticity theory of Flegr (class V), suggests that adaptive evolution in sexual species is operative shortly after the emergence of a species by peripatric speciation – while it is evolutionary plastic. To a major degree, i.e. throughout 98-99% of their existence, sexual species are evolutionarily frozen (class III) or elastic (class IV and V) on a microevolutionary time scale and evolutionarily frozen on a macroevolutionary time scale and can only wait for extinction, or the highly improbable return of a population segment to the plastic state due to peripatric speciation. The punctuational theories have many evolutionary and ecological implications. Most of these predictions could be tested empirically, and should be analyzed in greater depth theoretically. The punctuational theories offer many new predictions that need to be tested, but also provide explanations for a much broader spectrum of known biological phenomena than classical gradualistic evolutionary theories. REVIEWERS: This article was reviewed by Claus Wilke, Pierre Pantarotti and David Penny (nominated by Anthony Poole).